ANALISIS PENGELOLAAN DAN PENERAPAN PEMBELAJARAN E-LEARNING DI SEKOLAH DASAR KABUPATEN SAMBAS PADA MASA PANDEMI - Rizki Pratama Putra; Nurul Hidayati Murtafiah; Dewi Yanti; Mansur (UNISAN JURNAL, 2024)
Based on government demands in the world of education today, e-learning is implemented to support online learning using internet network devices. Sambas Elementary School utilizes Madrasah e-learning in online learning. For this reason, it is necessary to analyze the management and implementation of e-learning in elementary schools in Sambas Regency. The subjects of this research were 1 subject content expert, 1 learning design expert, 1 learning media expert, and 27 students for the trial. The data collection methods used are document recording, questionnaires and tests. The data analysis techniques used are qualitative descriptive analysis, quantitative descriptive analysis and inferential statistical analysis (t-test). The results of the research show that the validity of the e-learning developed is declared valid with each assessment (a) the results of the review of learning content experts with a percentage of 95.00% in the very good category (b) the results of the review of learning design experts with a percentage of 92.72% in the category very good, (c) learning media expert review results with a percentage of 91.11% in the very good category, (d) results of individual trials with a percentage of 92.98% in the very good category, (e) results of small group trials with a percentage of 91 .46%, and (f) field trial results with a percentage of 92.53% in the very good category. The resulting e-learning is of very good qualification, so it is feasible and effective to apply in the learning process to improve student learning outcomes.